Evolution of the deformation profile of a horizontal thin ethanol layer when heated locally; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Spesivtsev S. Serafim (2017, 2017)
Title screen